Self-Confidence Moderates the Effect of Emotional Intelligence and Reading Interest on the Level of Accounting Understanding: Case Study on Accounting Students of STIE PPI Campus Balaraja - Atika Purnamasari; Andrean Eko Haryoko (JOURNAL INTELEKTUAL, 2024)
Introduction/Main Objectives: To analyze and find out whether Emotional Intelligence, Reading Interest, Level of Accounting Understanding and Self-Confidence in Accounting Students of STIE PPI Campus Balaraja. Background Problems: The success of high accounting understanding is the attitude and mentality and the ability to read oneself in relation to the personal psychology aspects of students in developing their personalities and this understanding is often termed Emotional Quotient (EQ). Novelty: Adding a moderation variable, namely self-confidence in encouraging the level of accounting understanding with moderate interaction. Research Methods: Using a quantitative method with a correlation research design with SPSS as a tool in measuring the variables studied, in testing the moderation, the Moderate Regression Analysis (MRA) interaction approach is used. Finding/Results: There is a significant influence on the Level of Accounting Understanding, Reading Interest in Accounting Students of STIE PPI Balaraja Campus both partially and simultaneously, the results of the MRA analysis show that self-confidence has no influence on the Level of Accounting Understanding. Conclusion: With good emotional intelligence, students can more quickly understand learning on campus to the maximum.